Commodification of Religious Sites and Transparency of Public Financial Management: A Study of The Grave Site of Sunan Gunung Djati Cirebon, West Java - Upit, Gupita (Al-Hikmah, 2025)
This study examines the phenomenon of commodification of religious sites and transparency of public financial management at the tomb of Sunan Gunung Djati. This religious site is not only spiritually meaningful, but also gives rise to economic circulation through various forms of fund receipts such as donations, donation boxes, and tomb entrance tickets. However, the fund management system is considered not yet transparent, thus giving rise to negative prejudices from the community. This study uses a qualitative approach through observation, interviews, and literature studies to obtain more in-depth data. The results of the study show that religious sites have a dual function as spiritual spaces and sources of community economy which are currently still managed traditionally. Therefore, a more transparent, collaborative, and accountable financial management system is needed to maintain the sustainability of the spiritual, social, and economic values ​​of the religious site.